Early laparoscopic cholecystectomy reduces hospital stay in mild gallstone pancreatitis. A randomized controlled trial. Issue 1 (January 2020) - Riquelme, Francisco; Marinkovic, Boris; Salazar, Marco; Martínez, Waldo; Catan, Felipe; Uribe-Echevarría, Sebastián; Puelma, Felipe; Muñoz, Jorge; Canals, Andrea; Astudillo, Cristian; Uribe, Mario
Abstract: Background: Two strategies for same-admission cholecystectomy in mild gallstone pancreatitis (MGP) exist: early surgery (within 48–72 h from admission) and delayed surgery until resolution of symptoms and normalization of pancreatic tests. Methods: This was a single-center, open-label RCT. Patients with MGP according to revised Atlanta classification-2012 and SIRS criteria were randomly assigned to early laparoscopic cholecystectomy (E-LC) within 72 h from admission or delayed laparoscopic cholecystectomy (D-LC). Laparoscopic-endoscopic rendezvous was performed when common bile duct stones were found at systematic intraoperative cholangiography. The primary outcome was length of stay (LOS), and the secondary outcomes were complications at 90 days, need for ERCP/choledocolithiasis, conversion, and re-admission. One year of follow-up was carried-on. Results: At interim analysis, 52 patients were randomized (26 E-LC, 26 D-LC). E-LC versus D-LC was associated with a significantly shorter LOS (median 58 versus 167 h; P  = 0.001). There were no differences in ERCP necessity for choledocolithiasis between the two approaches (E-LC 26.9% versus D-LC 23.1%, P  = 1.00). No differences in postoperative complications were found. Conclusions: E-LC approach in patients with MGP significantly reduced LOS and was not associated with clinically relevant postoperative complications. Trial registration: clinicaltrials.gov (NCT02590978 ).